Victim Initiated Positive Disengagement: How Victims Can Flourish in the Aftermath of a Crime - Holloway, Amy R (2012)
The relationship between a crime victim and an offender is unlike any other relationship: it is involuntary and initiated during a traumatic event. This has special implications for how the relationship is resolved. This paper looks at the history of the victim label and identifies the limitations of the criminal justice system for addressing many victims’ needs. The principles of positive psychology and such constructs as resilience, post-traumatic growth, and the theory of well-being are explored; and examples are given of how these principles and constructs are used by victims to help them flourish. This paper identifies theories of relationship dissolution and applies them to the hypothesis that a victim initiated positive disengagement process is a strategy that victims can use in the aftermath of the crime to help them heal and thrive. This has significant implications for the types of services that post-conviction victim service programs provide and for further research into this topic